Low-Cost Contact Angle Measurement System for QCM Sensor - Setyawan Purnomo Sakti; Rizal Y Aji; Layli Amaliya; Masruroh Masruroh (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2017)
Hydrophobicity is one of the importance factors in the surface properties of materials. This work presents the development of a low-cost contact angle measurement system based on goniometric measurement using a low-cost digital camera, tilt control system for surface alignment and curvature approximation algorithm to determine the contact angle between the solid and spherical cap of a water droplet. The design is specifically targeted for measuring the contact angle of a Quartz Crystal Microbalance sensor in the form of HC-49/U with a disc diameter of 8.7mm.The contact angle measurement using goniometric measurement depends on the quality of captured image and calculation method for the angle determination. Proper alignment of the sample surface is required to minimize the discrepancy of the angle measurement of water drop surface profile caused by gravity. A PIC18F4550 microcontroller is used to control the motorized tilt platform to reduce the discrepancy between left and right contact angle value. Circle fit algorithm to determine the contact angle value from the captured image is used. Using the motorized tilt control system and circle fit algorithm, the developed contact angle measurement system able to measure the contact angle with discrepancy less than 1O.